Boosting Second Harmonic Radiation from AlGaAs Nanoantennas with Epsilon-Near-Zero Materials - Davide Rocco (Applied Sciences, 2018)
Enhancing the second harmonic conversion efficiency at the nanoscale is a critical challenge in nonlinear optics. Here we propose the use of epsilon-near-zero materials to boost the nonlinear radiation in the far field. Here, a comparison of the second harmonic behavior of a cylindrical AlGaAs nanoantenna placed over different semi-infinite layers is presented. In particular, we observed that the second harmonic generation is strongly enhanced and redirected by the simultaneous presence of a resonance at the fundamental wavelength and a low-permittivity condition in the substrate at the harmonic wavelength. Our results pave the way for a novel approach to enhance optical nonlinearities at the nanoscale.